A critical analysis of the unity movement in Bangladesh: Shaikh Azizur Rahman’s “unity in diversity" - Huq, Fayzul; Arshad Islam, Islam (2019)
Muslims in Bangladesh are polarised and disunited, including among Islamist groups, who are supposed to be the symbol of Muslim Unity. Shaikh Azizur Rahman Nesarabadi (1915-2008) was a pioneering figure who propelled the theory and practise of uniting the people of Bangladesh. According to him, ittihad mal Ikhtelaf (Unity in Diversity) is the only solution to existent disunity. This paper analyses his discourse and his role in the politics and society of Bangladesh by textual analysis of primary and secondary data. After analysing Unity in Diversity itself, we provide a short biographical sketch of Shaikh Azizur Rahman, showing his exposure to both Shariah and Sufi education, and their impacts on his thought. The paper then focuses on his ideas on four stages of unity and analyses them in light of contemporary social realities in Bangladesh and the Muslim world. This paper concludes that Shaikh Nesarabadi’s thought and theory on unity depend upon three elements: moderation and mutual respect, focus on common interest, and the Tawhidic paradigm. These comprise the framework for Muslim unity whose adoption by Muslims can fulfil the command of Allah to enable the Ummah to resume a leading role in the world as a champion of justice.